Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3390/brainsci11091162
|View full text |Cite
|
Sign up to set email alerts
|

Neuroanatomical Correlates of Binge-Eating Behavior: At the Roots of Unstoppable Eating

Abstract: Binge-eating refers to episodes of uncontrolled eating accompanied by a perceived loss of control, which can be common in the general population. Given the profound negative consequences of persistent binge-eating such as weight and eating disorders, it is vital to determine what makes someone more vulnerable than others to engage in such a conduct. A total of 42 normal-weight individuals (21 with binge-eating episodes and 21 without binge-eating episodes) underwent a structural magnetic resonance imaging meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Structural and functional neuroimaging studies among this subclinical population suggested a pattern of hemispheric asymmetry in cortical excitability of the prefrontal areas with the left prefrontal cortex described as a key region for inhibitory control processes in overeating (Yokum et al, 2011;Val-Laillet et al, 2015;Gluck et al, 2017;Stice and Burger, 2019;Oliva et al, 2021). In particular, Dong and colleagues (Dong et al, 2016), in their fRMI study, suggest a positive correlation between the activation of the left dorsolateral prefrontal cortex (lDLPFC) and the impulse control compensation in response to a stronger reward signal among women with an elevated impulse to restrictive eating.…”
Section: Introductionmentioning
confidence: 86%
“…Structural and functional neuroimaging studies among this subclinical population suggested a pattern of hemispheric asymmetry in cortical excitability of the prefrontal areas with the left prefrontal cortex described as a key region for inhibitory control processes in overeating (Yokum et al, 2011;Val-Laillet et al, 2015;Gluck et al, 2017;Stice and Burger, 2019;Oliva et al, 2021). In particular, Dong and colleagues (Dong et al, 2016), in their fRMI study, suggest a positive correlation between the activation of the left dorsolateral prefrontal cortex (lDLPFC) and the impulse control compensation in response to a stronger reward signal among women with an elevated impulse to restrictive eating.…”
Section: Introductionmentioning
confidence: 86%
“…When it comes to PET, there are three studies that investigate serotonin transporter availability with one of them also looking at dopamine transporter availability (Galusca et al, 2014;Kuikka et al, 2001;Tauscher et al, 2001). There are three studies that look at GMV or the cerebral surface of patients with BN (Berner et al, 2018;Marsh et al, 2015;Oliva et al, 2021). There are another four studies looking at resting-state functional connectivity (Domakonda et al, 2019;Lavagnino et al, 2014;Lee et al, 2014;Spalatro et al, 2019).…”
Section: Limitationsmentioning
confidence: 99%